The importance of student monitoring in academic learning: a two-year follow-up - Gabriel Pereira Nunes; Beatriz Ommati Pirovani; Hiago Guimarães Silva; Ana Victória Butarelo; Juliana da Silva Rossini; Jefferson Martins Costa; Larissa Pereira Nunes; Karina Vieira Martins (Universidade Estadual de Campinas, 2018)
Monitory's exercises must provide conditions that support academic and personal development for students in graduation, once the leveling possibilities in a way that monitors can fill the demand of students in previous seasons. Aim: This study has the goal to investigate the monitory's value in benefit of student's good scholar performance. Methods: In 2015 and 2016 second year Odontology students were monitored for the subject pharmacology. Facing need of accompanied study because high fails percentage. Accompanied theory classes were did weekly, study groups and content review to deal with. After two years of accompany was determined that percentage number of fails. The data were analyzed by variance and Student-Newman-Keuls test (p<0,001). Results: Majority had expressive results, since number of reproves decreased drastically, statically lower than in antecedent years. Conclusion: It was possible to prove that activity has a positive effect in learning for learners making possible access to knowledge and was indispensable for the regiments systematization, seen that advice and monitory students make them develop better skills to learn the disciplines.